1986
DOI: 10.1111/j.1399-0004.1986.tb01260.x
|View full text |Cite
|
Sign up to set email alerts
|

The Borjeson‐Fbrssman‐Lehmann syndrome

Abstract: The propositus of this report presents a peculiar dysmorphic syndrome associated with severe mental retardation and epileptic attacks. Morphological stigmata include a round, fatty face with large, somewhat protruding tongue, large normally formed ears, relative microcephaly, abundant abdominal fat, dwarfism with hyperkyphosis and short neck. Analogous phenotypic abnormalities were present in the mother and a maternal cousin. The clinical and familial findings in this apparently rare mental retardation syndrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1989
1989
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…BFLS is an X-linked dominant disease characterized by late-childhood truncal obesity, severe intellectual disability, epilepsy, microcephaly, long ears, short stature, and gynecomastia [53]. Affected males manifest hypotonia, failure to thrive, big ears, and small external genitalia as infants and moderately short stature with emerging truncal obesity, gynecomastia, macrocephaly, tapering fingers, and shortened toes as boys.…”
Section: Bçrjeson-forssman-lehmann Syndrome (Bfls)mentioning
confidence: 99%
“…BFLS is an X-linked dominant disease characterized by late-childhood truncal obesity, severe intellectual disability, epilepsy, microcephaly, long ears, short stature, and gynecomastia [53]. Affected males manifest hypotonia, failure to thrive, big ears, and small external genitalia as infants and moderately short stature with emerging truncal obesity, gynecomastia, macrocephaly, tapering fingers, and shortened toes as boys.…”
Section: Bçrjeson-forssman-lehmann Syndrome (Bfls)mentioning
confidence: 99%
“…The phenotype of MNS overlaps with that of serpentine fibula-polycystic kidney syndrome (SFPKS: MIM 600330) a rare condition characterized by growth retardation, dysmorphism, hirsutism, short neck, elongated bowed fibulae, metatarsus adductus, polycystic kidneys, deafness and normal intelligence. To date, only three sporadic cases (two females, one male) have been reported as having SFPKS (Dereymaeker et al, 1986;Exner, 1988) The sibs reported by Rosser et al (1996) with this diagnosis are considered by some to be examples of Frank-ter Haar syndrome despite the dysmorphism being atypical for this condition (Maas et al, 2004).…”
Section: Introductionmentioning
confidence: 94%
“…This may explain why most papers focussed on physical appearance and less attention was paid to behaviour. In general, behaviour varied from hyperactivity, expressed aggression, self‐injury and difficulties to control behaviour, to friendly, pleasant and cooperative (Dereymaeker et al. 1986; Turner et al.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Intellectual functioning in heterozygous females has been described from normal to moderate ID (Börjeson et al 1962;Robinson et al 1983;Ardinger et al 1984;Dereymaeker et al 1986;Petridou et al 1997;Kubota et al 1999;Baumstark et al 2003;Turner et al 2004;Valleé et al 2004;Crawford et al 2006). The frequency of significant learning problems was estimated to occur in 20% (Turner et al 2004).…”
Section: Cognitionmentioning
confidence: 99%
See 1 more Smart Citation